Cascaded Förster Resonance Energy Transfer and Role of Relay Dyes - Namboodiri, C. K. R.; Bisht, Prem B.; Dantham, V. R. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
The effect of introducing a relay dye on the energy transfer efficiency in a new donor-acceptor system has been studied. The values of the critical transfer distance, the reduced concentration, and the energy transfer efficiency of the cascaded system (consisting of three dyesdonor-relay dye-acceptor) are compared with that of the two dye system. Experimentally, it has been observed that the presence of a relay dye increases the transfer efficiency from the donor to the acceptor.